Dinamika Ekonomi dalam Konflik Perang: : Tafsir Ibnu Ashur tentang Ghanīmah dan Dampaknya pada Ekonomi Modern - Zainuddin, Moch; A. Halil Thahir (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
This article explores the dynamics of ghanīmah, the wealth gained by Muslim armies from their enemies during warfare and its modern-day context, through the interpretive lens of Ibnu Ashur. It further explores how principles derived from ghanīmah can inform contemporary economic policy, address issues of inequality and foster social solidarity after conflict. By linking historical interpretations of ghanīmah to modern economic challenges, this study offers valuable insights into the potential of Islamic economic principles to contribute to a fairer global economy. This research is qualitative in nature with a descriptive-analytical approach, with the methodology used being library research, with primary sources being Ibnu Ashur's Tafsir al-Taḥrīr wa al-Tanwīr, and secondary sources including books, journals, scientific articles, and other relevant documents. Ghanīmah goes beyond mere material acquisition, serving as a mechanism for wealth redistribution aimed at restoring social and economic balance in the post-conflict context. Ibnu Ashur's analysis emphasizes the importance of justice and social responsibility, especially in protecting vulnerable groups such as orphans, the poor, and relatives of the Prophet Muhammad.